Novobiocin Analogs as Potential Anticancer Agents - Dlugosz, Angelika; Janecka, Anna (Mini Reviews in Medicinal Chemistry, 2017)
Background: The aminocoumarin antibiotic, novobiocin, is a natural product that inhibits DNA gyrase, a bacterial enzyme involved in cell division. Method: More recently, novobiocin was found to act also on eukaryotic cells by blocking the 90 kDa heat shock protein (Hsp90). Hsp90 is a molecular chaperone, critical for folding, stabilization and activation of many proteins, in particular oncoproteins responsible for cancer progression. As opposed to the geldanamycin and radicicol, the known inhibitors of Hsp90 that bind to the N-terminal region, the binding domain of novobiocin is localized in the C-terminal part of this protein. While the N-terminal inhibition also leads to the induction of some pro-survival signals, C-terminal inhibitors in which prosurvival responses are avoided and client degradation is maintained can be developed as a new class of potential anticancer chemotherapeutics. Numerous novobiocin analogs have been designed in the search for more potent compounds and some of them exhibit significantly enhanced anti-proliferative activity versus the natural product, as evaluated by cellular efficacies against several cancer cell lines. Conclusion: This review describes structure-activity-relationships of novobiocin analogs and some biological data reported so far on the anticancer activity of these modified compounds.
Keywords: Antiproliferative activity